Koreografi Tari Dolalak di Kelompok Arum Manis, Kecamatan Kutoarjo, Kabupaten Purworejo - Wiranti, Avira; Putri, Rimasari Pramesti (Dinasti Research, 2025)
Central Java. One of the cultural groups that continues to preserve the existence of Dolalak is the Arum Manis group. The Dolalak Dance performed by the Arum Manis group uses the logungan style, also known as the Kulonan version, which symbolizes strength and resilience. The logung movement is derived from martial arts or pencak silat movements that have been slowed down and simplified. This study aims to describe the choreography of Dolalak Dance as performed by the Arum Manis group in Kutoarjo Subdistrict, Purworejo Regency. The choreography in this research refers to the theory proposed by Y. Sumandiyo Hadi (2012:41). The study uses a qualitative descriptive method with an ethnocoreological approach. Data collection techniques include observation, interviews, and documentation. The data were analyzed qualitatively using triangulation techniques. This research was conducted at the Arum Manis group in Pacor Village, Kutoarjo Subdistrict, Purworejo Regency. The results of the study show that the choreographic process of Dolalak Dance in the Arum Manis group consists of three main stages: (1) exploration, (2) improvisation, and (3) formation. There are 12 types of movement in the choreography og Dolalak Dance performed by the Arum Manis group.